Evaluation of Primary Screening Test for Platelet Homeostasis in Patients with Chronic Kidney Disease (Bangladesh Journal of Medicine, 2013)
This observational study was done on 50 cases of predialytic chronic kidney disease (CKD) patients. The aim of the study was to determination of total platelet count and bleeding time, comparison of the platelet count and bleeding time with the severity of chronic kidney disease. The mean age of the patients was 41.22±2.0 years, mean haemoglobin 4.96 ±0.32gm/dl, serum creatinine430.74± 11.92 ?mol/L, platelet count 246.50 ± 13.63x109/L and bleeding time were 4.13± 0.28 min respectively. Thrombocytopenia (9min) 6(12%) cases , among them only 4(8% ) cases were thrombocytopenic. There was no significant relationship between platelet count and serum creatinine. No correlation was found between platelet count and bleeding time. No significant correlation was also found in Bleeding time and creatinine. Therefore, it can be concluded that platelet count is highly variable in chronic kidney disease and it is not a reliable screening test for bleeding diathesis in chronic kidney disease patients. Bleeding time is the best platelet function test that correlates clinical bleeding.DOI: http://dx.doi.org/10.3329/bjmed.v21i2.13610 Bangladesh J Medicine 2010; 21: 55-57